Dynamics of an $n$-Patch Predator-Prey Model with Allee Effect (Journal of Nonlinear Modeling and Analysis, 2025)
A class of $n$-patch predator-prey diffusion models with the Alleeeffect is established. The influence of the Allee effect and diffusion of prey onthe existence and stability of the equilibrium point are investigated. Firstly,sufficient conditions for the permanence and extinction of the system are analyzed. Secondly, by constructing a new Lyapunov function in terms of graphtheory, we obtain a sufficient condition of the global asymptotical stability forthe positive equilibrium point. Finally, our results of this paper are verifiedby Matlab simulation.
Keywords: $n$-patch; stability; Allee effect; predation-prey model.